Backfat Thickness at First Insemination Affects Litter Size at Birth of the First Parity Sows - Atthaporn Roongsitthichai; Seri Koonjaenak; Padet Tummaruk (Agriculture and Natural Resources, 2010)
The present study was undertaken to investigate the influence of backfat thickness (BF) at the first insemination on the litter size at birth of the first parity sows. In total, 249 Landrace × Yorkshire crossbred gilts were measured for BF at the last rib, about 6-8 cm away from the dorsal midline (P2) by A-mode ultrasonography. The BF measurement was performed three times on the gilts: the first day of insemination; the 70th day of the gestation period; and 1 w prior to the expected farrowing day. The gilts were categorized into three groups based on BF measured on the first insemination day: high (BF ≥ 17.0 mm, n=75), moderate (BF = 14.0-16.5 mm, n=121) and low (BF ≤ 13.5 mm, n=53). The results revealed that the average BF of the gilts was 15.4 ± 2.3, 17.7 ± 2.7, and 20.1 ± 2.9 mm on the first insemination day, the 70th day of gestation, and 1 w before farrowing, respectively. The gilts in the high group had a higher total number of piglets born per litter (TB; 13.1 ± 0.4) than those in the moderate group (12.0 ± 0.4, P = 0.04), and tended to have higher TB than those in the low group (12.1 ± 0.6, P = 0.1).